2009
DOI: 10.1016/j.bmc.2009.09.047
|View full text |Cite
|
Sign up to set email alerts
|

Removal of the 20-methyl group from 2-methylene-19-nor-(20S)-1α,25-dihydroxyvitamin D3 (2MD) selectively eliminates bone calcium mobilization activity

Abstract: The 18-nor (7), 21-nor (8) and 18,21-dinor (9) analogs of (20S)-1α,25-dihydroxy-2-methylene-19-norvitamin D3 (6, 2MD) were prepared by convergent syntheses. The known phosphine oxide 10 was coupled by the Wittig–Horner process with the corresponding C,D-fragments (13–15), obtained by a multi-step procedure from commercial vitamin D2. The goal of our studies was to examine the influence of removal of the methyl groups located at carbons 13 and 20 on the biological potency of 2MD in the hope of finding analogs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…S9), which shows that both 20(OH)D 2 and 1,20(OH) 2 D 2 metabolites overlap with the native ligand well and bind to the VDR with high affinity. The presence of the 20-OH moiety contributes to the binding with increased van der Waals interaction and provides a unique ability to reduce the hypercalcemic effects for this type of analog, which is consistent with literature reports that certain modifications at C20 are very beneficial for reducing hypercalcemia (4,30,31,36,64), as well as with our present (Fig. 10) and previous studies (61).…”
Section: Discussionsupporting
confidence: 82%
“…S9), which shows that both 20(OH)D 2 and 1,20(OH) 2 D 2 metabolites overlap with the native ligand well and bind to the VDR with high affinity. The presence of the 20-OH moiety contributes to the binding with increased van der Waals interaction and provides a unique ability to reduce the hypercalcemic effects for this type of analog, which is consistent with literature reports that certain modifications at C20 are very beneficial for reducing hypercalcemia (4,30,31,36,64), as well as with our present (Fig. 10) and previous studies (61).…”
Section: Discussionsupporting
confidence: 82%
“…Further studies have confirmed that this configuration, in the presence of a full-length side chain, improves binding of specific proteins to the VDR transcriptional complex (Schwinn and DeLuca, 2007). Furthermore, replacement of the 20-methyl with hydrogen did not affect VDR binding or transcriptional activity, but it did eliminate the mobilization of calcium from bone while leaving intestinal calcium transport intact (Barycki et al, 2009). A clinical trial was performed on groups of osteopenic women (placebo, 220 ng of 2MD, and 440 ng of 2MD) to measure the effect of daily oral treatment with 2MD on BMD, serum markers of bone turnover, and safety for 1 year.…”
Section: Vitamin D Receptor Modulatorsmentioning
confidence: 88%
“…The VDR is expressed in a number of cell types in the skin, including the keratinocyte (Stumpf et al, 1979;Hosomi et al, 1983;Pillai et al, 1988;Reichrath et al, 1997). All of the 2-methylene-19-nor-1,25(OH) 2 D 3 and D 2 analogs tested bind with high affinity to the VDR, and have been shown to be transcriptionally active in reporter cell systems (Sicinski et al, 2002;Plum et al, 2004;Barycki et al, 2009; see Table 1 footnote). However, the compounds that are most effective in inducing comedolysis do not have the highest affinity to the VDR.…”
Section: Discussionmentioning
confidence: 95%
“…The structure and activities of 19-nor analogs of 1,25(OH) 2 D 3 and D 2 containing a 25-hydroxylated side chain and modified to contain a methylene group in the 2-carbon position are shown in Table 1. All of them bind with high affinity to the vitamin D receptor (VDR) in vitro, activate transcription, and induce bone calcium mobilization, and intestinal calcium transport in vivo (Sicinski et al, 2002;Barycki et al, 2009; see the patent information described in the section Chemicals under Materials and Methods). The dose of drug used to test for activity in skin was based on in vivo potency, with the goal of using a dose that would produce a 1.0-3.0 mg per 100 ml increase in serum calcium level to ensure sufficient drug exposure.…”
Section: 25(oh) 2 D 3 Does Not Induce Comedolysismentioning
confidence: 99%